Knowledge, Attitude and Practice (KAP) on Oral Health among students of Nepalese Army Institute of Health Sciences - Gurung, Meenakshi; Sen Malla, Sudha; Rajbhandari, Bipul; Bajracharya, Barsha (Medical Journal of Shree Birendra Hospital, 2022)
Background: Oral health plays an important role in the overall health of the individual. Both medical and nursing students are expected to possess good oral health awareness and work together for public health promotion especially in developing countries like Nepal. The aim of the study is to assess and compare Knowledge, Attitude and Practice (KAP) on Oral Health among students of Nepalese Army Institute of Health Sciences (NAIHS) Methods: This is a cross sectional questionnaire based study conducted at Nepalese Army Institute of Health Sciences, from 2020.10.15 to 2021.04.15. A total of fourteen standard structured close ended questionnaire was sent to all the medical and nursing students in g- mail to assess and compare KAP on Oral Health. Result: Among 200 MBBS students, 157, 184, 200 had knowledge about sugar, bacteria and not brushing respectively which causes dental caries and 163 had knowledge about benefits of fluoride on dental health. On the other hand out of 200 nursing students 147, 178, 200 had knowledge about sugar, bacteria and not brushing respectively which causes dental caries and 152 had knowledge about benefits of fluoride on dental health. On an average 88% of MBBS students had good knowledge about dental caries whereas 84.62% of nursing students had good knowledge about dental caries. More of nursing students had attitude of visiting dentist in a year than medical students whereas more of medical students had never visited a dentist. Among 200 MBBS students 143 (71.5%) were found brushing twice daily, 121 (60.5%) brushes after every meal (i.e. morning and night), 35 (17.5%) followed proper vertical tooth brushing technique and as for the duration of brushing 104 (52%) brushed for 2 min. On the other hand, among 200 nursing students 152 (76%) were found brushing twice daily, 132 (66%) brushes after every meal, 43 (21.5%) followed proper vertical tooth brushing technique and as for the duration of brushing 116 (58%) brushed for 2 min. Conclusion: Based on the present study the total knowledge on dental caries was found to be significantly higher in MBBS students than nursing students however nursing students had more positive attitudes towards oral health. Oral health practice of nursing students in terms of frequency of brushing, times, method and duration of brushing was also found to be comparatively better than MBBS students. With proper knowledge of oral health behavior, medical and nursing students can play an important role in the oral health education of individuals and groups and act as role models for patients, friends, families and the community at large.